DESAIN DAN ANALISIS PEKERJAAN DALAM MANAJEMEN PERSONALIA - Masturah Minabari (Paedagogia: Jurnal Pendidikan, 2018)
Each work design also influences the employee's attitude towards the task at hand. In addition, job design determines work relations between employees, between employees and superiors, types of work, and socio-economic relations. Through design work is carried out changing the content, functions and relations of work that are able to complete in accordance with the target and boss satisfaction. Job design and analysis includes; authority of the office holder, routine implementation of duties, identity of the holder, and involvement of the incumbent. Job functions include; work methods used, work coordination, responsibility, information flow, and work authority. While employment relations include joint work activities between officials and all employees in one agency. Keywords: official management, design work, design